La morphologie karstique dans le canyon de la Cèze et sur le plateau de Méjannes-le-Clap (Garrigues nord, Gard, France) – Rapports avec l'évolution paléogéographique mio-pliocène - Joël Jolivet; Claude Martin (Physio-Géo)
The limestone Méjannes-le-Clap plateau is incised by the Cèze canyon. A study of the plateau has shed new light on the paleogeographic evolution of the south-western edge of the French Massif Central between the development of the Miocenian erosion surface and the Pleistocene. The incision of the Cèze in the late Miocene cannot be attributed to the dessication of the Mediterranean Sea during the Messinian (5.9/5.3 Ma), which did result in the incision of the Rhône canyon (236 m bsl). It is clear that Messinian retrogressive erosion stopped at the edge of the Rhône valley. Therefore, the incision of the Cèze canyon predates the Messinian. It goes back certainly to the superior Burdigalian, in agreement with the model of evolution proposed by D. BESSON (2005) for the "Rhodano-Provençal" basin. This incision was followed in the Miocene by two phases of removing sediment (infra-Tortonian and Messinian), each occurring after a phase of filling.Traces left by lithophagous molluscs after flooding of the canyon during the Pliocene transgression can be found at various elevations between 135 and 160 m, due to later tectonic movements. During the Pliocene, the canyon filled up with land deposits that subsist today in the form of mostly quartzose pebbles embedded in reddish matrix rock, up to elevations of 245 m. Outliers of Pliocene alluvial formations subsist on shoulders and benches that are remnants from the Cèze canyon's different hollowing phases. Some of these topographical elements include subhorizontal karst systems at elevations of 180-220 m asl. The cavities with ascending passages that emerge by shafts at an altitude near 280 m are linked, for their part, to the Miocene transgression and/or filling phases.The most useful information about the sector's Messinian and Pliocene evolution is provided by other karst systems composed of subhorizontal and inclined passages with connecting-shafts. As with the Saint-Marcel Cave in Ardèche (L. MOCOCHAIN et al., 2006-a, 2006-b), these systems are the result of ascending karst genesis. The subhorizontal passages located at about 100 m asl under the Méjannes-le-Clap plateau must be interpreted in relation to the level reached by the Cèze canyon after it was hollowed out. These passages are currently functional, the base level being only a few metres below the level of superior Miocene hollowing. The Pliocene transgression caused karst formation to shift upwards to 140150-m asl. Some of the systems formed as a result of the accumulation of Pliocene terrestrial deposits. At elevations between 130 and 230 m asl, parts of some of the networks are filled in with allochthonous deposits. Deep galleries roughly follow the canyon layout. Downstream of the gorges, divers have reached depths of -35 m bsl in the Marnade system. This deep network developed in connection with the incision of the Rhône canyon. As along the southern edge of the Cévennes (M. SÉRANNE et al., 2002), the sinking of the karst reduced or even eliminated surface runoff, which explains why retrogressive erosion cannot have penetrated far back into the Cèze valley.